The rakess - Peckham, Scarlett (Peckham, Scarlett. Society of Sirens, 2020)
"Meet the Society of Sirens--three radical, libertine ladies determined to weaponize their scandalous reputations to fight for justice and the love they deserve ... She's a Rakess on a quest for women's rights ... Seraphina Arden's passions include equality, amorous affairs, and wild, wine-soaked nights. To raise funds for her cause, she's set to publish explosive memoirs exposing the powerful man who ruined her. Her ideals are her purpose, her friends are her family, and her paramours are forbidden to linger in the morning. He's not looking for a summer lover ... Adam Anderson is a wholesome, handsome, widowed Scottish architect, with two young children, a business to protect, and an aversion to scandal. He could never, ever afford to fall for Seraphina. But her indecent proposal--one month, no strings, no future--proves too tempting for a man who strains to keep his passions buried with the losses of his past. But one night changes everything ... What began as a fling soon forces them to confront painful secrets--and yearnings they thought they'd never have again. But when Seraphina discovers Adam's future depends on the man she's about to destroy, she must decide what to protect ... her desire for justice, or her heart."--Provided by publisher.